Ferenczi's turn in psychoanalysis - Giampieri-Deutsch, Patrizia; Bókay, Antal; Rudnytsky, Peter L. (New York University Press, 1996)
Sigmund Freud's role in the history and development of psychoanalysis continues to be the standard by which others are judged. One of the most remarkable features of that history, however, is the exceptional caliber of the men and women Freud attracted as disciples and coworkers. One of the most influential, and perhaps overlooked, of them was the Hungarian analyst Sndor Ferenczi. Apart from Freud, Ferenczi is the analyst from that pioneering generation who addresses most immediately the concerns of contemporary psychoanalysts.